Vitamin D, Depressive Symptoms, and Covid-19 Pandemic - Ceolin, Gilciane; Mano, Giulia Pipolo Rodrigues; Hames, Natália Schmitt; Antunes, Luciana da Conceição; Brietzke, Elisa; Rieger, Débora Kurrle; Moreira, Júlia Dubois (Frontiers in Neuroscience, 2021)
Since the COVID-19 outbreak, studies across diverse countries have strongly pointed toward the emergence of a mental health crisis, with a dramatic increase in the prevalence of depressive psychopathology and suicidal tendencies. Vitamin D deficiency has been associated with an increased risk of mental health problems as well as individual responses to stress. Studies have discussed the relationship between low serum vitamin D concentrations and depressive symptoms, suggesting that maintaining adequate concentrations of serum vitamin D seems to have a protective effect against it. Vitamin D was found to contribute to improved serotonergic neurotransmission in the experimental model of depression by regulating serotonin metabolism. The signaling of 1,25-dihydroxyvitamin D3, the active form of vitamin D, through vitamin D receptor (VDR) induces the expression of the gene of tryptophan hydroxylase 2 (TPH2), influences the expression of serotonin reuptake transporter (SERT) as well as the levels of monoamine oxidase-A (MAO-A), the enzyme responsible for serotonin catabolism. Vitamin D also presents a relevant link with chronobiological interplay, which could influence the development of depressive symptoms when unbalance between light-dark cycles occurs. In this Perspective, we discussed the significant role of vitamin D in the elevation of stress-related depressive symptoms during the COVID-19 pandemic. It is suggested that vitamin D monitoring and, when deficiency is detected, supplementation could be considered as an important healthcare measure while lockdown and social isolation procedures last during the COVID-19 pandemic.